Ability and Stability of Running and Walking in Children with Cerebral Palsy - Iosa, Marco; Morelli, Daniela; Marro, Tiziana; Paolucci, Stefano; Fusco, Augusto (Neuropediatrics, 2013)
Objectives Many studies have examined how children with cerebral palsy (CP) manage to walk, but few have investigated running, yielding controversial results. The aim of this study was to quantitatively assess gait ability and its stability in children with hemiplegic CP while running and walking. Methods A group of 20 children with spastic hemiplegia due to CP (CPG, 5.1 ± 2.3 years old), and a group of 20 children with typical development (TDG, 5.9 ± 2.6 years old) underwent a 10-m walking/running test with a wearable triaxial accelerometer fixed to their lower trunk. Spatiotemporal gait parameters, root mean squares of upper body acceleration, and related harmonic and symmetry ratios were computed. Results Differences in gait speed were significantly higher during running ( – 19% for CPG with respect of TDG) than during walking ( – 14%, p = 0.028). Conversely, no significant changes were observed in terms of gait stability, and the differences in terms of gait harmony along anteroposterior axis recorded during walking ( – 43%, p < 0.001) disappeared during running ( + 3%, p = 0.834). Conclusions During running, children with CP are slower than children with TD, but their gait was not less stable, and the harmony of their anteroposterior movements was even more similar to TDG than during walking.
Keywords: cerebral palsy; gait; kinematics; accelerometry; sport